Combination anti-PD1 and ipilimumab therapy in patients with advanced melanoma and pre-existing autoimmune disorders. Issue 5 (7th May 2021) - Brown, Lauren J; Weppler, Alison; Bhave, Prachi; Allayous, Clara; Patrinely Jr, J. Randall; Ott, Patrick; Sandhu, Shahneen; Haydon, Andrew; Lebbe, Celeste; Johnson, Douglas B; Long, Georgina V; Menzies, Alexander A; et al.
Abstract : Background: Clinical trials of immunotherapy have excluded patients with pre-existing autoimmune disease. While the safety and efficacy of single agent ipilimumab and anti-PD1 antibodies in patients with autoimmune disease has been examined in retrospective studies, no data are available for combination therapy which has significantly higher toxicity risk. We sought to establish the safety and efficacy of combination immunotherapy for patients with advanced melanoma and pre-existing autoimmune diseases. Methods: We performed a retrospective study of patients with advanced melanoma and pre-existing autoimmune disease who received combination ipilimumab and anti-PD1 at 10 international centers from March 2015 to February 2020. Data regarding the autoimmune disease, treatment, toxicity and outcomes were examined in patients. Results: Of the 55 patients who received ipilimumab and anti-PD1, the median age was 63 years (range 23–83). Forty-six were treated with ipilimumab and nivolumab and nine with ipilimumab and pembrolizumab. Eighteen patients (33%) had a flare of their autoimmune disease including 4 of 7 with rheumatoid arthritis, 3 of 6 with psoriasis, 5 of 10 with inflammatory bowel disease, 3 of 19 with thyroiditis, 1 of 1 with Sjogren's syndrome, 1 of 1 with polymyalgia and 1 of 1 with Behcet's syndrome and psoriasis. Eight (44%) patients ceased combination therapy due to flare. Thirty-seven patients (67%) had an unrelated immune-related adverse event (irAE), and 20 (36%) ceased combination immunotherapy due to irAEs. There were no treatment-related deaths. Patients on immunosuppression (OR 4.59; p=0.03) had a higher risk of flare. The overall response rate was 55%, with 77% of responses ongoing. Median progression free survival and overall survival were 10 and 24 months, respectively. Patients on baseline immunosuppression had an overall survival of 11 months (95% CI 3.42 to 18.58) compared with 31 months without (95% CI 20.89 to 41.11, p=0.005). Conclusions: In patients with pre-existing autoimmune disease, not on immunosuppression and advanced melanoma, combination ipilimumab and anti-PD1 has similar efficacy compared with previously reported trials. There is a risk of flare of pre-existing autoimmune disorders, particularly in patients with inflammatory bowel disease and rheumatologic conditions, and patients on baseline immunosuppression.